Charizomenos Hērōdēi: Josephus’ Nicolaus of Damascus in the Judaean Antiquities - Teets, Sarah Christine (Histos, 2013)
Approaching Nicolaus of Damascus in Josephus’ Judaean Antiquities as first and foremost Josephus’ literary creation rather than merely his historical source, this paper explores the complexity of Josephus’ representation of Nicolaus both as a historical source and as a historical actor in the AJ, and argues that it is largely determined by Josephus’ political aims (pro-Judaean apologetic and ethical protreptic) and rhetorical techniques. This results in a discrepancy between Josephus’ tone toward Nicolaus in the earlier portion of the AJ and in the account of Herod, in which the actor and historian are unified in their negative characterization as defender and advocate of Herod’s interests.